Faucian bargain : the most powerful and dangerous bureaucrat in American history - Deace, Steve; Erzen, Todd (Post Hill Press, 2021)
Can liberty survive in the hands of one all-powerful, unchallenged, and unelected bureaucrat? It wasn't too long ago that the average American didn't know who Anthony Fauci was. Now, after the coronavirus has spread nationwide, he's arguably the most powerful bureaucrat in American history. But is it dangerous for a free society to concentrate so much power in the hands of an unelected official? Who or what holds Fauci accountable? (back cover)